Structural characterization and reaction mechanism of the Ti/SiC gradient material with Mg2Si additive fabricated by reaction sintering - Jingkun Li; Binguo Fu; Tianshun Dong; Guolu Li; Yanling Zhang; Yongyue Liu; Jiageng Liu (Journal of Materials Research and Technology, 2023)
The Ti/SiC gradient material with Mg2Si additive was designed and fabricated by reaction sintering. The structure, microstructure and properties were investigated systematically. The result indicated that the Ti/SiC gradient material contained six layers with Ti-rich and Si-rich regions. The relative density decreased from 98.32% to 88.73%, and it increased to 97.28%. Besides, the harness increased from 532.97 HV to 571.32 HV and reduced to 228.14 HV with the increase of Ti content. The fracture toughness of the SiC layer was 6.74 MPa m1/2, and it decreased to 4.91–5.39 MPa m1/2 at the layers containing Ti. The shrinkage rates increased during heating, and it slowed down at the holding stage. The densification primarily occurred at the heating and holding stages. The densification mechanism is the pore displacement controlled by lattice diffusion. Ti5Si3 synthesized by the reaction between Ti and SiC shows the incoherent interface to the Ti grain.